2018
DOI: 10.1186/s12870-018-1256-y
|View full text |Cite
|
Sign up to set email alerts
|

Three endoplasmic reticulum-associated fatty acyl-coenzyme a reductases were involved in the production of primary alcohols in hexaploid wheat (Triticum aestivum L.)

Abstract: BackgroundThe cuticle covers the surface of the polysaccharide cell wall of leaf epidermal cells and forms an essential diffusion barrier between the plant and the environment. The cuticle is composed of cutin and wax. Cuticular wax plays an important role in the survival of plants by serving as the interface between plants and their biotic and abiotic environments, especially restricting nonstomatal water loss. Leaf cuticular waxes of hexaploid wheat at the seedling stage mainly consist of primary alcohols, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 77 publications
(98 reference statements)
3
26
0
Order By: Relevance
“…In the present study, we further found that various adverse conditions or stresses, including low temperature and drought, induced TaCER1‐1A expression within hours and led to increased accumulation of alkanes in wheat wax. This finding is similar to previous reports on other plant species, where diverse wax biosynthesis genes were found induced by stress conditions as well as plant hormones involved in stress responses: Drought, osmotic stress, or ABA treatment strongly induced expression, for example, of the Arabidopsis CER6 and CER1 genes (Bourdenx et al, ; Hooker, Millar, & Kunst, ; Kosma et al, ) and of diverse wax biosynthesis genes in bread wheat and Brachypodium (Chai et al, ; Wang, et al, 2015b; Wang, et al, 2015c; Wang et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the present study, we further found that various adverse conditions or stresses, including low temperature and drought, induced TaCER1‐1A expression within hours and led to increased accumulation of alkanes in wheat wax. This finding is similar to previous reports on other plant species, where diverse wax biosynthesis genes were found induced by stress conditions as well as plant hormones involved in stress responses: Drought, osmotic stress, or ABA treatment strongly induced expression, for example, of the Arabidopsis CER6 and CER1 genes (Bourdenx et al, ; Hooker, Millar, & Kunst, ; Kosma et al, ) and of diverse wax biosynthesis genes in bread wheat and Brachypodium (Chai et al, ; Wang, et al, 2015b; Wang, et al, 2015c; Wang et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Similar effects were also observed for rice and cucumber CER1 homologs (Wang, Zhang, Xu, Ren, et al, 2015;Zhou et al, 2013). Overall, our results confirmed that genes (Bourdenx et al, 2011;Hooker, Millar, & Kunst, 2002;Kosma et al, 2009) and of diverse wax biosynthesis genes in bread wheat and Brachypodium (Chai et al, 2018;Wang, et al, 2015b;Wang, et al, 2015c;Wang et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations